Shelterbelts int he service of sheep farming - Díaz Fernández, Daniel; Csízi, István (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The harmful effects of the climate change induce an even greater challenge in terms of sheep farming in Hungary. Predictably in order to ensure the effectiveness of animal producing, we have to create appropriate conditions to the sheeps and keep them in their comfort zone. From the point fo view of animal husbandry it is essential to choose the perfect area and optimize the surroundings during the heat days and the rumination period between two grazings. In our experiment – using a Conrad WH2080 type radio-controlled weather station – we continuously recorded and evaluated the datas of temperature, air humidity, and air flow rates at the surface and at the height of 1 meter in a poplar shelterbelt and in a deep bedded barn. The results based on precise instrument confirm the positive impacts of shelterbelts in extensive sheep farming.